Contribution to the knowledge of the butterfly fauna (Lepidoptera: Rhopalocera) of the Šentvid plateau, NW Slovenia - Torkar, Gregor (Acta entomologica slovenica (Ljubljana), 2013)
The paper presents butterfly fauna (Lepidoptera: Rhopalocera) of the Šentvid plateau, an insufficiently surveyed part of Slovenia located at an altitude between 600-900 m a.. Altogether 76 butterfly species were recorded on five locations. Among them 10 are threatened and four are protected species. Despite short period of observations relatively high number of butterfly species was observed for this altitude. Most probable explanation for butterfly species richness is that Šentvid plateau is reasonably well-maintained and south oriented cultural landscape, with extensive meadows and mixed forests, and with a mild climate, particularly the favourable precipitation regime in summer months, maintaining vegetation of the grasslands green.
Keywords: butterflies; butterfly diversity; conservation; favna; metulji; ohranjanje; Slovenia; Slovenija; Šentvid plateau; Šentviška planota